Influence of secretome from porcine cardiosphere-derived cells on porcine macrophage polarization and their possible implications for cardiac remodeling post-myocardial infarction in vitro - Pulido, M.; de Pedro, M. A.; Marchena, A. M.; Alvarez, V.; Casado, J. G.; Sanchez-Margallo, F. M.; López, E. (Frontiers in Cell and Developmental Biology, 2025)
The inflammatory response plays a crucial role in tissue repair following myocardial infarction (MI), with macrophages being central regulators of inflammation and tissue remodeling. Macrophage polarization between pro-inflammatory M1 and anti inflammatory M2 phenotypes significantly influences inflammation and tissue repair. This study evaluates the effect of the secretome from porcine cardio sphere-derived cells (S-CDCs) on macrophage polarization and its downstream impact on endothelial cells (HUVECs) and cardiac fibroblasts (PCF). Macrophages were treated with the secretome from S-CDCs, and their polarization status was assessed. Conditioned media from treated macrophages were applied to HUVECs and PCFs to evaluate effects on migration, wound healing, and fibrotic activity. Additionally, transcriptomic profiling of S-CDCs was performed to identify relevant cytokines. S-CDCs induced a mixed M1/M2 phenotype in macrophages, attenuating M1-associated inflammation without fully promoting M2 characteristics. Conditioned medium from S-CDC-treated M1 macrophages enhanced migration and wound healing in HUVECs, indicating proangiogenic effects. In contrast, medium from M2 macrophages did not show similar activity. Additionally, S-CDC-treated M1 macrophage medium modulated the migratory and fibrotic behavior of PCFs. Transcriptomic analysis revealed a cytokine profile enriched in pro-reparative factors such as VEGFA, TGFB, and CCL2. These findings suggest that S-CDCs modulate macrophage polarization to promote tissue repair and angiogenesis while minimizing excessive inflammation. This highlights their potential as a therapeutic strategy to enhance cardiac regeneration following MI.